Dynamics of changes in the biomechanical characteristics of the snatch technique with increase in the weight of the projectile under competition conditions - Khasin L.A.; Gross E.R. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to assessment and comparison of spatio-temporal and kinematic characteristics of the barbell jerk performed with various weights. Methods and structure of the study. To achieve this goal, the approaches of 13 athletes of the Russian national team were analyzed in competition conditions using high-speed video filming as part of a survey of competitive activity by a comprehensive scientific group in weightlifting. The results obtained were assessed in order to detect reliably significant differences between the spatio-temporal and kinematic characteristics between the approaches. Results and conclusions. The results obtained indicate that with an increase in the weight of the projectile, the speed characteristics of the snatch technique significantly decrease, which corresponds to Hill’s law, and this, as a consequence, affects the decrease in the height of the approach of the bar at the end of the final acceleration, at the end of the unsupported phase and the maximum height of the approach of the bar, as well as at the time of reaching maximum speed. As the weight of the projectile increases, athletes need to exert greater forces to maintain kinematic and spatiotemporal characteristics. An important conclusion is the need to use 95–100% of the weights in order for the spatio-temporal and kinematic characteristics to reach the required values as a result of training.